If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(16 + 2) = -8(6 + -1x) Combine like terms: 16 + 2 = 18 0.5(18) = -8(6 + -1x) Multiply 0.5 * 18 9 = -8(6 + -1x) 9 = (6 * -8 + -1x * -8) 9 = (-48 + 8x) Solving 9 = -48 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9 + -8x = -48 + 8x + -8x Combine like terms: 8x + -8x = 0 9 + -8x = -48 + 0 9 + -8x = -48 Add '-9' to each side of the equation. 9 + -9 + -8x = -48 + -9 Combine like terms: 9 + -9 = 0 0 + -8x = -48 + -9 -8x = -48 + -9 Combine like terms: -48 + -9 = -57 -8x = -57 Divide each side by '-8'. x = 7.125 Simplifying x = 7.125
| 4a-5b+3a+4b= | | 3*7y=10x | | -15x+15=12x | | 4x+4y=432 | | 5a+2b+3a= | | -7b-7(3b+4)= | | (x/4)^20 | | f(x)=Log(4x+12) | | 2-10=x/-7 | | 2a-4b+3b+3a= | | 3a^5-39a^3+108a=0 | | 4a-2x+7a-x= | | 2y=-13(x-5) | | 2x-3y+x-4y= | | 3x-5y-(-3x)= | | 3a+b-(-2b)= | | 4a-5c+3a-c= | | 2a+3x-4x-5a= | | 9+b=c+3a | | -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 |